The Hippo Signaling Pathway and Cancer - Oren, Moshe.; Oren, Moshe.; Aylon, Yael.; Aylon, Yael. (Springer New York : Imprint: Springer, 2013)
The Hippo signaling pathway is rapidly gaining recognition as an important player in organ size control and tumorgenesis. This volume presents virtually all aspects of tumor biology because members of the Hippo Pathway have been associated with numerous well-established cell signaling pathways, just to name a few; Rho, Wnt, TGFbeta and p53. Hippo signaling is not solely involved in regulating “classic” tumor characteristics such as cell proliferation, survival and growth, but is also diversely involved in cell-autonomous and non-cell-autonomous differentiation, migration and organ size control. With the multitude of signaling events mediated by the Hippo pathway and the vastly different functions that it plays, it is evident that these tumor suppressors are unique governors of cellular homeostasis. This timely volume gathers wide-ranging and burgeoning information on the Hippo pathway and its role in cancer into an accessible format of a single book.With the multitude of signaling events mediated by the Hippo pathway and the vastly different functions that it plays, it is evident that these tumor suppressors are unique governors of cellular homeostasis. This timely volume gathers wide-ranging and burgeoning information on the Hippo pathway and its role in cancer into an accessible format of a single book.